Sanguinarine protects against indomethacin-induced small intestine injury in rats by regulating the Nrf2/NF-κB pathways - Lin, Xiu-lian; Shi, Ya-ning; Cao, Yu-ling; Tan, Xi; Zeng, Ya-ling; Luo, Shi-teng; Li, Ya-mei; Qin, Li; Xia, Bo-hou; Fu, Rong-geng; Lin, Li-mei; Li, Kai; et al. (Frontiers in Pharmacology, 2022)
In recent years, small intestine as a key target in the treatment of Inflammatory bowel disease caused by NSAIDs has become a hot topic. Sanguinarine (SA) is one of the main alkaloids in the Macleaya cordata extracts with strong pharmacological activity of anti-tumor, anti-inflammation and anti-oxidant. SA is reported to inhibit acetic acid-induced colitis, but it is unknown whether SA can relieve NSAIDs-induced small intestinal inflammation. Herein, we report that SA effectively reversed the inflammatory lesions induced by indomethacin (Indo) in rat small intestine and IEC-6 cells in culture. Our results showed that SA significantly relieved the symptoms and reversed the inflammatory lesions of Indo as shown in alleviation of inflammation and improvement of CMDI and TDI scores. SA decreased the levels of TNF-α, IL-6, IL-1β, MDA and LDH in small intestinal tissues and IEC-6 cells, but increased SOD activity and ZO-1 expression. Mechanistically, SA dose-dependently promoted the expression of Nrf2 and HO-1 by decreasing Keap-1 level, but inhibited p65 phosphorylation and nuclear translocation in Indo-treated rat small intestine and IEC-6 cells. Furthermore, in SA treated cells, the colocalization between p-p65 and CBP in the nucleus was decreased, while the colocalization between Nrf2 and CBP was increased, leading to the movement of gene expression in the nucleus to the direction of anti-inflammation and anti-oxidation. Nrf2 silencing blocked the effects of SA. Together our results suggest that SA can significantly prevent intestinal inflammatory lesions induced by Indo in rats and IEC-6 cells through regulation of the Nrf2 pathway and NF-κBp65 pathway.